Effect of neuromuscular balance on static balance in adult and elderly populations - Tartari, Ana Paula; Moreira, Felipe Figueiredo; Pereira, Mário César Da Silva; Kerppers, Ivo Ilvan; Cidral-Filho, Francisco José; Salgado, Afonso Shiguemi Inouse (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction: Postural control has two behavioral goals: postural balance and orientation, which are achieved through a dynamic relationship between sensory information and muscle activity. To maintain body balance, the vestibular, optical and proprioceptive systems must be fully functioning. Neuromuscular balance (NB), developed by François Soulier, is a non-manipulative method that involves applying a soft vibration or a micro-thrust with a small mechanical device to a joint or vertebra in order to induce realignment and readjustment. Objective: To identify the biomechanical effect of NB upon static balance and body oscillations of adults and the elderly through stabilometry. Methodology: In this interventional study, 20 healthy volunteers - 10 young adults (aged between 18 and 30 years old) and 10 elderly (aged between 60 and 80 years old) - were subjected to 10 consecutive weekly NB sessions. Stabilometry was assessed at baseline and after the 10th intervention (center of pressure (COP) behavior parameters: total area in mm2, laterolateral and anteroposterior width in mm). Results: Anteroposterior as well as total area oscillations significantly decreased in the adult population (p<0.0179 and p<0.0242, respectively). Additionally, all parameters were reduced in both groups, although differences between pre and post intervention were not statistically significant. Conclusion: NB effectively decreased anteroposterior and total area oscillations of adult patients, positively contributing to static balance.